Operation of a hybrid modular multilevel converter during grid voltage unbalance - Amankwah, Emmanuel K.; Watson, Alan James; Clare, Jon C. (IET, 2016)
The recently proposed parallel hybrid modular multilevel converter is considered to be a low loss, low component count converter with soft switching capability of the ‘main’ H-bridge. The converter has similar advantages to other emerging modular multilevel converter circuits being considered for HVDC power transmission and can be made compact which is desirable for offshore application. However, during ac network unbalance the individual ‘chain-links’ exchange unequal amounts of power with the grid which requires appropriate remedial action. This paper presents research into the performance of the converter and proposes a suitable control method that enables the converter to operate during grid voltage unbalance. The proposed control concept involves the use of asymmetric third harmonic voltage generation in the ‘chain-links’ of the converter to redistribute the power exchanged between the individual ‘chain-links’ and the grid. Mathematical analysis and simulation modelling with results are presented to support the work described.